1995
DOI: 10.1074/jbc.270.38.22218
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity Maturation of Anti-4-hydroxy-3-nitrophenylacetyl Mouse Monoclonal Antibody

Abstract: To understand the mechanism of affinity maturation, we examined the antigen-antibody interactions between 4-hydroxy-3-nitrophenylacetyl (NP) caproic acid and the Fab fragments of three anti-NP antibodies, N1G9, 3B44, and 3B62, by isothermal titration calorimetry. The analyses have revealed that all of these interactions are mainly driven by negative changes in enthalpy. The enthalpy changes decreased linearly with temperature in the range of 25-45°C, producing negative changes in heat capacity. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Mutations in the Vernier zone residues may contribute to structural adjustment of the CDR regions upon binding; however, enthalpy-entropy compensation may interfere with the improvement of the antibody affinity for its target. Enthalpyentropy compensation has been observed in previous pioneering studies of the thermodynamics of affinity maturation of antibodies; an energetic barrier originating from the relationship between enthalpy and entropy changes is overcome by an increase in negative enthalpy changes, a decrease in negative entropy changes during the affinity maturation process, or both (80). Note that affinity maturation of antibodies leads to a decrease in the structural changes of the antibody upon binding (81).…”
mentioning
confidence: 89%
“…Mutations in the Vernier zone residues may contribute to structural adjustment of the CDR regions upon binding; however, enthalpy-entropy compensation may interfere with the improvement of the antibody affinity for its target. Enthalpyentropy compensation has been observed in previous pioneering studies of the thermodynamics of affinity maturation of antibodies; an energetic barrier originating from the relationship between enthalpy and entropy changes is overcome by an increase in negative enthalpy changes, a decrease in negative entropy changes during the affinity maturation process, or both (80). Note that affinity maturation of antibodies leads to a decrease in the structural changes of the antibody upon binding (81).…”
mentioning
confidence: 89%
“…Many studies show that hydrogen bonds play a significant role in a wide range of biomolecular interactions in terms of generating affinity and specific recognition (26 -31). It is also reported that hydrogen bonds can make a favorable enthalpic contribution to protein-ligand interactions (32)(33)(34). Thus, the subject of hydrogen bonding is of major interest in biological research.…”
mentioning
confidence: 99%
“…However, thermodynamic analysis of antigen-antibody interaction for analyzing precisely the contribution of noncovalent forces to the interaction is most suitable (17)(18)(19)(20)(21)(22), especially when combined with site-directed mutagenesis of structurally well defined ones (23)(24)(25). We have focused on the interaction of hen egg white lysozyme (HEL 1 ) with the anti-HEL monoclonal antibody Hy-HEL10 interaction as a model of proteinaceous antigen-antibody interaction (26,27).…”
mentioning
confidence: 99%